CO2–CH4 conversion and syngas formation at atmospheric pressure using a multi-electrode dielectric barrier discharge. Issue 9 (March 2015) - Ozkan, A.; Dufour, T.; Arnoult, G.; De Keyzer, P.; Bogaerts, A.; Reniers, F.
Abstract: The conversion of CO2 and CH4 into value-added chemicals is studied in a new geometry of a dielectric barrier discharge (DBD) with multi-electrodes, dedicated to the treatment of high gas flow rates. Gas chromatography is used to define the CO2 and CH4 conversion as well as the yields of the products of decomposition (CO, O2 and H2 ) and of recombination (C2 H4, C2 H6 and CH2 O). The influence of three parameters is investigated on the conversion: the CO2 and CH4 flow rates, the plasma power and the nature of the carrier gas (argon or helium). The energy efficiency of the CO2 conversion is estimated and compared with those of similar atmospheric plasma sources. Our DBD reactor shows a good compromise between a good energy efficiency and the treatment of a large CO2 flow rate.